Preservice Teachers’ Perceptions of Science Literacy through Indigenous Science in Sasaknese Traditional Games: A Comparative Study Based on Gender and Semester - Sukarso, AA; Yamin, Muhammad; Muliadi, Agus (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to investigate compare the perceptions of preservice teachers regarding the use of indigenous science in Sasaknese traditional games as a medium for strengthening science literacy based on gender and semester. This exploratory research was conducted at the Mandalika University of Education with a subject pool of 234 preservice teacher students. The research utilized a validated closed questionnaire instrument with responses gathered using a Likert scale. The data from this study were analyzed using t-test and Anova test. The results of this study are (1) There is no significant difference in the perceptions of male and female students regarding the use of indigenous science in Sasaknese traditional games as a medium for strengthening science literacy, as evidenced by a significance value of 0.899, which is greater than 0.05 (>0.05); (2) There is no significant difference in the perceptions of third, fifth, and seventh-semester students regarding the use of indigenous science Sasaknese traditional games as a medium for strengthening science literacy, as indicated by a significance value of 0.114, which is greater than 0.05 (>0.05).